Odpowiedź :
Odpowiedź:
1)=-7x
2) -3x-4x= -7x
3) 6y-(-y)=6y+y=7y
4)3xy-7x+5y-3y= 3xy-7x+2y
5)x-2x-(-6)+x+4= 2x+10
6) -2ab+8+ab-(-9)=-ab+17
7)4,5b-3,4c+1,6c-1,5b= 3b-1,8c
8) 15x-6y+8-5x-2y-7-2x-4=8x-8y-3
9) (a+2ab)-(2a-b)-(2a-b)-(a-3b)= a+2ab-2a+b-2a+b-a+3b= -4a+2ab5b
10) (2ab+a+7)-(4ab-a+4)= 2ab+a+7-4ab+a-4= -2ab +2a+3
Szczegółowe wyjaśnienie:
wydaje mi się ze jest dobrze
1. -3x-4x=2 2. -3x-4x=3 3. 6y -(-7y)= 4 4. 3xy-7x+5y-3y=5
-7x=2| :(-7) -7x=3| :(-7) 13y=4| :13 3xy-7x+2y=5
x= -2/7 x= -3/7 y= 4/13 ↑ to jest wynik
5.x-2x-(-6)+x+4=6 6.-2ab+8+ab -(-9)= 7
0x+10=6| -10 ab+17=7 | -17
0x= -4 ab= -10